Economic value and pricing of water in agriculture - Kasnakoglu H. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
The subject of this paper is to suggest a methodology to evaluate the economic value of water which can be used as a basis for water pricing. The methodology involves the use of agricultural sector models incorporating water as a scarce input. The economic value of water for different land types, regions and crops are estimated from the shadow prices of water and irrigated land constraints. After a theoretical discussion, the paper will also present the results of such a model applied to the South-eastern Anatolia Project (GAP) Region in Turkey, which is one of the world's largest irrigation and integrated regional development projects. Changes and differences in land values as a result of irrigation will be presented towards the estimation of the economic value of water
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)